2009
DOI: 10.1177/1043986209344561
|View full text |Cite
|
Sign up to set email alerts
|

The Giant That Never Woke

Abstract: This article argues that discretionary parole is the lynchpin to improved correctional practice. Calls to abolish discretionary parole have failed to consider its potential to steer correctional agendas toward sustainable evidence-based practices (EBPs) and effective reentry/transitional services. The history of corrections and parole is marked by tension between the goals of warehousing and correcting prisoners. Notwithstanding a growing body of impressive research that clarifies the importance of the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Petersilia () argues that the parole dossier should include a report on the crimes committed by prisoners as well as the institutional rehabilitation report. Paparozzi and Guy () contend that crucial consideration could include the likelihood of prisoners’ positive conduct in the community upon release. Abadinsky () asserts that the Board must be satisfied that a prisoner presents an acceptable risk to public safety and that adequate arrangements are in place for the prisoner in the community.…”
Section: Rehabilitation In Prison and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Petersilia () argues that the parole dossier should include a report on the crimes committed by prisoners as well as the institutional rehabilitation report. Paparozzi and Guy () contend that crucial consideration could include the likelihood of prisoners’ positive conduct in the community upon release. Abadinsky () asserts that the Board must be satisfied that a prisoner presents an acceptable risk to public safety and that adequate arrangements are in place for the prisoner in the community.…”
Section: Rehabilitation In Prison and Challengesmentioning
confidence: 99%
“…Parole has been established for the purpose of rehabilitating prisoners and successfully reintegrating them back into the community (Champion ). The importance of releasing prisoners under the parole system is to identify prisoners who have the best chance for rehabilitation while serving their sentence, and those who pose the least threat to public safety (Paparazzi and Guy ). Who is to be paroled is a question that has vital importance in the field of corrections today and the parole selection process by the Parole Board members has grave consequences on the effectiveness of the entire parole system (Cromwell and Del Carmen ).…”
mentioning
confidence: 99%
“…Findings from numerous studies (Gottfredson, Mitchell-Herzfeld, & Flanagan, 1982;Paparozzi & Guy, 2009;Schlager & Robbins, 2008;Solomon, Kachnowski, & Bhati, 2005) have demonstrated that discretionary release and subsequent PO supervision has a significant positive impact in terms of offender outcomes. For instance, in an examination of the factors associated with successful sentence completion, Grant and Gillis (1999) found that the successful completion of day parole was associated with a reduction in both parole revocation rates, and general recidivism rates.…”
Section: Description Of Relevant Offender Populationsmentioning
confidence: 99%
“…Nevertheless, as alluded to above (e.g., Caplan, 2007, Public Safety Canada, 2014 evidence that parole board members adhere to empirically established criteria is equivocal. Instead of relying primarily on actuarial methods, which have generally been found to be more accurate, liberal, and reliable than clinical methods (Grove, Zald, Lebow, Snitz, & Nelson, 2000), decisions appear to involve personal ideologies and at least some degree of subjectivity (Paparozzi & Guy, 2009 (Pardoel, 2013). These findings are consistent with similar research conducted in the U.S. (Morgan & Smith, 2005;Proctor, 1999 (Andrews, Bonta, & Wormith, 2006;Barklage, Miller & Bonham, 2006;Skeem & Manchak, 2008).…”
Section: The Role Of Parole Officers In the Release Decision Making Pmentioning
confidence: 99%